Challenges and Opportunities of Implementing Differentiated Instruction amid the COVID-19 Pandemic: Insights from a Qualitative Exploration - Suet-Ying Yuen; Zili Luo; Sally Wai-yan Wan (MDPI AG, 2023)
Differentiated instruction (DI) has been introduced as a viable approach for accommodating the diverse learning needs of students in the same classroom. Despite the significant advantages attributed to this approach, it can still be a challenge for teachers to incorporate DI into practice. This study examined the lived experiences and perceptions of teachers regarding the influence of the COVID-19 pandemic on their differentiation practices. Purposive sampling was used, and 40 in-service primary and secondary school teachers in Hong Kong were recruited. Hybrid thematic analysis was implemented to examine data from the semi-structured interviews carried out in both face-to-face and online formats. Drawing on the five-dimensional model of differentiation as a conceptual framework, the findings were organized into five thematic areas: (1) teaching arrangements, (2) learning environment, (3) teaching methods, (4) support materials, and (5) assessment. The perceptions of teachers, both positive and negative, regarding the impact of the pandemic on DI were categorized into sub-themes. The results indicated that while the pandemic brought about considerable obstacles for educators in practicing DI, it also opened up opportunities for new approaches to meeting the diverse needs of students.